2004
DOI: 10.1007/s10396-004-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and computed tomography of extracapsular invasion in cervical lymph nodes of squamous cell carcinoma in the oral cavity

Abstract: Diagnostic images are effective for the preoperative diagnosis of extracapsular invasion of metastatic cervical nodes of carcinoma of the oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Sonographic features, including node matting, perinodal edema, and indeterminate lymph node margins, have a high specificity for the prediction of ECS in axillary lymph nodes of patients with biopsy-proved breast cancer. 27 Only 1 study 28 has been published in the English literature to date on the use of ultrasonography for the detection of cervical ECS in patients with HNSCC. In an analysis of 47 patients, ultrasonography had a sensitivity and specificity of 80% and 74%, respectively, for the detection of macroscopic ECS.…”
Section: Discussionmentioning
confidence: 99%
“…Sonographic features, including node matting, perinodal edema, and indeterminate lymph node margins, have a high specificity for the prediction of ECS in axillary lymph nodes of patients with biopsy-proved breast cancer. 27 Only 1 study 28 has been published in the English literature to date on the use of ultrasonography for the detection of cervical ECS in patients with HNSCC. In an analysis of 47 patients, ultrasonography had a sensitivity and specificity of 80% and 74%, respectively, for the detection of macroscopic ECS.…”
Section: Discussionmentioning
confidence: 99%
“…However, PET/CT had a significantly higher sensitivity than CT and MRI. Only two studies examined the diagnostic accuracy of US [10,27] making it impossible to include the modality in the meta-analysis. Currently, no studies on the diagnostic value of PET/MRI exist.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…Full text review of these articles identified seven studies to be used for qualitative and quantitative analysis. [22][23][24][25][26][27][28] A summary of the search process is shown in Figure 1. All seven studies were of level 2 evidence based on the Oxford Level of Evidence criteria.…”
Section: Search Resultsmentioning
confidence: 99%
“…Initial screening by title and abstract left 65 studies. Full text review of these articles identified seven studies to be used for qualitative and quantitative analysis 22‐28 . A summary of the search process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%